Investigating the impact of persistent HPV infection on recurrence of lesions post-surgery for early-stage cervical cancer and related influencing factors - Na, Jing; Li, Ya; Lu, Qiao; Wang, Yang; Han, Shichao; Wang, Jun (Frontiers in Oncology, 2025)
ObjectiveTo explore the influencing factors of recurrence after surgical treatment for early-stage cervical cancer (stages IA1-IIA1) and to investigate the relationship between human papillomavirus (HPV) infection and postoperative recurrence of lesions.MethodsA retrospective analysis was conducted on the clinical data of 242 patients who underwent surgical treatment for early-stage cervical cancer (FIGO stages IA1-IIA1) at the Second Affiliated Hospital of Dalian Medical University between 2015 and 2022. Cox regression analysis was employed to evaluate the relationship between persistent postoperative HPV infection and lesion vaginal local recurrence while identifying the associated risk factors for persistent HPV infection following surgery.ResultsWithin 12 months postoperatively, the HPV clearance rate was 88.11%. HPV infection persisted beyond 12 months in 19 patients (7.9%), with 3 cases demonstrating the same HPV genotypes (types 52, 58) as those identified preoperatively. Multivariate analysis identified persistent postoperative HPV infection (odds ratio [OR] 1.72, 95% confidence interval [CI] -1.14 to 5, p=0.001*) as an independent risk factor for recurrence. Additionally, smoking (OR 7.49, 95% CI 1.19 to 47.13, p=0.032), abnormal vaginal microbiota (OR 0.663, 95% CI 0.403 to 1.088, p=0.001*), and the type of surgical procedure (OR 0.32, 95% CI 0.11 to 0.91, p=0.033) were significantly associated with a higher rate of persistent HPV infection.ConclusionPersistent HPV infection after surgery is an independent risk factor for postoperative recurrence in early-stage cervical cancer. Surgical approach, abnormal vaginal microbiota, and smoking are associated factors for persistent HPV infection after surgery.